Continuing Professional Development Model in the Schools Division of Sarangani - Roy Tribunalo; Gaudy C. Ortizo (East Asian Journal of Multidisciplinary Research, 2023)
This study explored and determined the extent of the Continuing Professional Development (CPD) implementation in government school institutions in the Sarangani Division for School Year 2022-2023. The 375 respondents from a total population of 6, 042 public school teacher were randomly selected across the 23 school districts. Based on the findings, the hypothesis on no significant relationship between the extent of the CPD implementation and the teacher’s competencies is accepted because of the Pearson’s r-value of -0.081 with negligible correlation 0.118 p-value. However, the hypothesis on no significant relationship between the contributing factors and the extent of CPD implementation is rejected and the model is a partial mediation. Sobel test yielded a z-value of -3.10600817 with a p-value of 0.00189631 that means significant at 0.05 level. Further, three major themes surfaced from the informant’s in-depth interview after an intensive analysis of the data gathered, namely: Limited Training Offered, Insufficient Execution of the Program, and Participatory Barriers to CPD Training. The indicated training need, preferred CPD modalities and pace, as well as monitoring, evaluation, and offering technical support to schools in terms of CPD may be taken into consideration by DepEd Offices. Hence, a CPD Model is recommended to take effect in the Schools Division of Sarangani to address the actual competency gap and relevant training needs for teachers’ professional growth and development.